Association of Polymorphisms in Estrogen Receptors with non-obstructive Azoospermia and Severe Secretory Oligozoospermia：a Meta-Analysis - Zhang, Aiqiao; Wang, Shangren; Liu, Li; Zhang, Zhexin; Pan, Yang; Niu, Shuai; Liu, Xiaoqiang (Urology Journal, 2025)
Purpose: Estrogen receptor (ER) genes play key roles in male and female reproduction. Non-obstructive azoospermia (NOA) and severe secretory oligozoospermia (SOL) are the most severe and complex conditions impacting male fertility. This meta-analysis aimed to study the association between PvuII ( rs2234693, 397T>C ), XbaI ( rs9340799, 351G>A ), AluI (1730G>A, rs4986938), and RsaI (1082G>A, rs1256049) polymorphisms and spermatogenic failure. Materials and Methods: The literature in PubMed, Medline, Embase, Web of Science, Cochrane Library, China Science and Technology Journal Database, WanFang data, and China National Knowledge Infrastructure databases were systematically searched, and a meta-analysis was conducted to investigate the association between polymorphism in estrogen receptors and spermatogenic failure. According to a set criterion, 10 studies were included for analyses. Results: ER α XbaI polymorphism was a decreased risk of NOA. The ER α PvuII polymorphisms does not associate with NOA and SOL. ER β AluI polymorphism increased the risk of NOA in Caucasian population. ER β RsaI polymorphism was a decreased risk of NOA and SOL in Caucasian males. Conclusion: The ER α XbaI and ER β RsaI polymorphisms are associated with the risk of NOA and SOL.